A mechanistic model on feeding-directional cutting force in surface grinding of CFRP composites using rotary ultrasonic machining with horizontal ultrasonic vibration. (May 2019) - Wang, Hui; Hu, Yingbin; Cong, Weilong; Hu, Zhonglue
Highlights: A cutting force model in RUM with horizontal ultrasonic vibration is explored. The tool-workpiece interaction is intermittent. The kinematic moving motions and trajectories of a single abrasive are discussed. The effective cutting time during one cycle of ultrasonic vibration is analyzed. The relationship between MRR and the impact force is established. Abstract: In surface grinding of carbon fiber reinforced plastic (CFRP) composites, cutting force is a key factor that controls surface damage, tool wear, cutting temperature, delamination, etc. Surface grinding of CFRP composites using rotary ultrasonic machining (RUM) with vertical ultrasonic vibration has been proven to be an effective method to reduce cutting force. However, the machined surface quality is lowered due to the knocking effects on the machined surface resulted from up-and-down vertical vibration. It has been proven that to decrease cutting force and simultaneously improve surface quality, ultrasonic vibration aligning with surface generation direction (feeding direction) is needed. However, there are limited investigations on RUM surface grinding of CFRP composites with horizontal ultrasonic vibration, and the mechanistic model on cutting force in such a process is not explored. This paper, for the first time, establishes a mechanistic model on feeding-directional cutting force in RUM surface grinding of CFRP composites with horizontal ultrasonic vibration. This modeling development is based on the assumption of brittle fracture material removal mechanism, which is the dominant removal mechanism in such a process. The predicted trends in this model agree well with those in experimentally measured results. This modeling will provide a guidance for the mechanistic modeling development to predict other output variables through the cutting force in RUM surface grinding of CFRP composites.